Hz Shop / Nurman Harith Al-Zikry Bustamam@Butaman - Bustamam@Butaman, Nurman Harith Al-Zikry (2021)
Hz Shop is an online shopping store that involves the sale of wet goods such as goat meat for which I have been an agent to sell it as my business for this subject. it is not an easy thing to do but it has given me education on business as a result of guidance from lecturers and people around. the item I’ve been selling is the “Pak Mat Western” marinated lamb which is definitely everyone’s favorite. I chose this thing to be a business because it is already known and even has its own name on its brand. many products have been released by this company. This business has started around April of 2021 which is appropriate the beginning things of this subject are studied. in addition, I have been taught by my sister in using social media such as facebook to start this business and managed to produce good results throughout this business.